Synthesis, Characteristics, and Field Applications of High-Temperature and Salt-Resistant Polymer Gel Tackifier - Guowei Zhou; Xin Zhang; Weijun Yan; Zhengsong Qiu (Gels, 2025)
To address the technical challenge of high polymer gel viscosity reducers losing viscosity at elevated temperatures and difficulty in controlling fluid loss, a polymer-based nano calcium carbonate composite high-temperature tackifier named GW-VIS was prepared using acrylamide (AM), 2-acrylamido-2-methylpropanesulfonic acid (AMPS), N-vinylpyrrolidone (NVP), and nano calcium carbonate as raw materials through water suspension polymerization. This polymer gel can absorb water well at room temperature and has a small solubility. After a long period of high-temperature treatment, most of it can dissolve in water, increasing the viscosity of the suspension. The structure of the samples was characterized by infrared spectroscopy, thermogravimetric analysis, and scanning electron microscopy, and their performance was evaluated. Rheological tests indicated that the 0.5% water suspension had a consistency coefficient (k = 761) significantly higher than the requirement for clay-free drilling fluids (k > 200). In thermal resistance experiments, the material maintained stable viscosity at 180 °C (reduction rate of 0%), and only decreased by 14.8% at 200 °C. Salt tolerance tests found that the viscosity reduction after hot rolling at 200 °C was only 17.31% when the NaCl concentration reached saturation. Field trials in three wells in the Liaohe oilfield verified that the clay-free drilling fluid supported formation operations successfully. The study shows that the polymer gel has the potential to maintain rheological stability at high temperatures by forming a network structure through polymer chain adsorption and entanglement, with a maximum temperature resistance of up to 200 °C, providing an efficient drilling fluid for deep oil and gas well development. It is feasible to select nano calcium carbonate to participate in the research of high-temperature resistant polymer materials. Meanwhile, the combined effect of monomers with large steric hindrance and inorganic materials can enhance the product’s temperature resistance and resistance to NaCl pollution.